Investigation of Leishmania cutanenous Antigens in blood Specimens - Aliaa Alnaimy; Ali B. M. Al-Waaly (Al-Qadisiyah Journal of Pure Science, 2021)
The study was conducted on 444 patients suffering from skin lesions of different ages and genders that were diagnosed by dermatologists as cutaneous leishmaniasis for people reviewing and throughout the days of the week for the department of epidemiology and transitional diseases who attended to hospitals in the city of Baghdad, namely (Al-Shaheed Dari Al Fayyad Teaching Hospital , Al-Shaheed Al Sadr Hospital , Al-Numan Teaching Hospital, Al-Karama Teaching Hospital) for the study period from October 1, 2019 until the end of March 2020.The methods of molecular diagnostics showed that multiplex pcr examined40 random samples of the parasite  that were collected throughthis technique from blood samples taken from the ulcers of infectedpeople to reveal the DNA parts of the Leishmania parasite. Specialprefixes for the Leishmania parasite species showed that 28 positive samplescontain the parasite's DNA and 12 negative samples, of which 11 are forthe Leishmania tropica type (27.5%) and 17 samples for the Leishmania major type(42.5%) at the molecular weight 1150 base pair.30 serum samples were taken from patients diagnosed with cutaneous leishmaniasis for serological tests. The current study showed a significant decrease in immunoglobulin G for patients with cutaneous leishmaniasis by 1205.100 ± 210.155 , The current results also showed a significant decrease in the level of immunoglobulin M in patients with cutaneous leishmaniasis by 90.366 ± 26.181